Correction: Calcite precipitation from by-product red gypsum in aqueous carbonation process. Issue 44 (18th April 2016) - Rahmani, Omeid; Tyrer, Mark; Junin, Radzuan
Abstract : Correction for 'Calcite precipitation from by-product red gypsum in aqueous carbonation process' by Omeid Rahmani et al., RSC Adv., 2014, 4, 45548–45557.